Futebol se aprende na escola : novas práticas de sociabilidade esportiva no contexto urbano. - Santos, Claudemir José dos (2007)
Our aim is to investigate the complex process of learning football in Brazil. The focus of our analysis will be an average size city in São Paulo countryside. Usually, this learning process is related to essential factors which are linked to the representations of playing typically brazilian football, that means a natural gift. Which is completely different from the process that is symbolically and materially built. We will focus our discussion in the phenomenon of the football schools , both the public and the private ones, as an example of co-participation in this process. The origin of these football schools in the seventies and eighties brought different conceptions about the way of playing, learning and representing football in the country. On the other hand, it increased the investments in social policies of leisure related to the youth. While we tried to understand this process, making use of theoretical instruments of Social Science, we could comprehend an important part of the sport sociability spread in some brazilian urban centers.